A Minimally Morphologically Destructive Approach for DNA Retrieval and Whole-Genome Shotgun Sequencing of Pinned Historic Dipteran Vector Species. (1st October 2021) - Korlević, Petra; McAlister, Erica; Mayho, Matthew; Makunin, Alex; Flicek, Paul; Lawniczak, Mara K N
Abstract: Museum collections contain enormous quantities of insect specimens collected over the past century, covering a period of increased and varied insecticide usage. These historic collections are therefore incredibly valuable as genomic snapshots of organisms before, during, and after exposure to novel selective pressures. However, these samples come with their own challenges compared with present-day collections, as they are fragile and retrievable DNA is low yield and fragmented. In this article, we tested several DNA extraction procedures across pinned historic Diptera specimens from four disease vector genera: Anopheles, Aedes, Culex, and Glossina . We identify an approach that minimizes morphological damage while maximizing DNA retrieval for Illumina library preparation and sequencing that can accommodate the fragmented and low yield nature of historic DNA. We identify several key points in retrieving sufficient DNA while keeping morphological damage to a minimum: an initial rehydration step, a short incubation without agitation in a modified low salt Proteinase K buffer (referred to as "lysis buffer C" throughout), and critical point drying of samples post-extraction to prevent tissue collapse caused by air drying. The suggested method presented here provides a solid foundation for exploring the genomes and morphology of historic Diptera collections.